2021
DOI: 10.1016/j.apsb.2021.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Boosting 5-ALA-based photodynamic therapy by a liposomal nanomedicine through intracellular iron ion regulation

Abstract: 5-Aminolevulinic acid (5-ALA) has been approved for clinical photodynamic therapy (PDT) due to its negligible photosensitive toxicity. However, the curative effect of 5-ALA is restricted by intracellular biotransformation inactivation of 5-ALA and potential DNA repair of tumor cells. Inspired by the crucial function of iron ions in 5-ALA transformation and DNA repair, a liposomal nanomedicine (MFLs@5-ALA/DFO) with intracellular iron ion regulation property was developed for boosting the PDT of 5-ALA, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…These results suggest the importance of tumor accumulation of chelators to enhance the PDT effects of 5‐ALA and the necessity of drug delivery systems. In this regard, recent study reported simultaneous delivery of DFO and 5‐ALA using liposomes for intravenous administration 24 ; however, we did not exploit a similar approach and utilized the oral administration of 5‐ALA. Since 5‐ALA is not stable in physiological pH and is usually manufactured/stored as chloride salt, it should not be intravenously injected to avoid acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest the importance of tumor accumulation of chelators to enhance the PDT effects of 5‐ALA and the necessity of drug delivery systems. In this regard, recent study reported simultaneous delivery of DFO and 5‐ALA using liposomes for intravenous administration 24 ; however, we did not exploit a similar approach and utilized the oral administration of 5‐ALA. Since 5‐ALA is not stable in physiological pH and is usually manufactured/stored as chloride salt, it should not be intravenously injected to avoid acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of ALA/PAMAM: PAMAM and ALA were stirred gently together at room temperature for 0.5 h, and then dialyzed with a 3500 Da dialysis bag to remove free ALA. Drug loading was determined by a published method, [2] and the most appropriate mass ratio of 1:5 between PAMAM and ALA was chosen for subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…[1] 5-aminolevulinic acid (ALA)-based free radical therapy has been approved by the Food and Drug Administration for clinical tumor treatment. [2,3] ALA, as the precursor of the endogenous photosensitizer protoporphyrin IX (PpIX), exhibits negligible photo toxicity. [4] Notably, ALA induces PpIX accumulation in mitochondria, [5][6][7] leading to 1 O 2 production specifically in the mitochondria, which amplifies the damage to tumor cells because the mitochondria are highly sensitive to free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Versatile nanoparticulate drug delivery systems (NDDSs) have attracted much attention because of their ability to deliver small or large molecule drugs efficiently. Various NDDSs with different components and structures, such as polymeric micelles, inorganic particles, vesicles or liposomes, prodrug, and so forth, could increase the drug solubility, reduce the uptake of the reticuloendothelial system, and target delivery to the desired location for high drug utilization and long circulation. PEG-polyester-based NDDSs were self-assembled from the biodegradable amphiphiles and approved by the Food and Drug Administration to be put into clinical tests, which were anticipated as potential drug vehicles in diabetes treatment in nanomedicine.…”
Section: Introductionmentioning
confidence: 99%